Effects of emotional expression and race familiarity on face identification - Lim, Joshua Wei Cong (Nanyang Technological University, 2020)
The study investigated the influence of emotional expressions (happy and angry) and race familiarity (Asian, Caucasian and Persian) on accuracy of face identification. In an incidental learning condition, participants were first presented with happy and angry faces of Asians, Caucasians and Persians. In a later recognition task, participants were instructed to recognise neutral equivalents of the aforementioned faces among other distractor faces. In general, results showed that recognition performance for happy faces was not significantly better than angry faces. However, differences in face recognition performance mediated by race familiarity reached significance. While recognition of Asian faces was not significantly better than Caucasian faces, both Asian and Caucasian faces were recognised more accurately than Persian faces. Further analysis suggested no interaction between race familiarity and emotional expression. While both happy and angry emotions were found to facilitate face identification to a similar extent, the findings from this study largely support the presence of the other-race effect as characterised by better recognition for Asian faces as opposed to Persian faces. Furthermore, findings also provide credibility to the contact hypothesis, with results showing that Caucasian faces were better identified than Persian faces.